Chronic supplementation of a multi-ingredient herbal supplement increases speed of cognitive task performance alongside changes in the urinary metabolism of dopamine and the gut microbiome in cognitively intact older adults experiencing subjective memory decline: a randomized, placebo controlled, parallel groups investigation - Wightman, Emma; Khan, Julie; Smith, Ellen; Rolfe, Vivien; Smith, Darren; Young, Greg; Cheung, William; Kennedy, David (Frontiers in Nutrition, 2023)
Background: The effects of herbs on brain function are often investigated in isolation, yet herbal preparations are often complex combinations of phytochemicals, designed to target widespread mechanisms. Objective: To assess the effects of chronic, 12- week, supplementation of a multi-ingredient herbal supplement (containing Bacopa monnieri, Gotu kola leaf, Turmeric whole powder, Reishi full spectrum, Rosemary, Cardamom, Holy Basil, Turmeric Wholistic™ extract, Green Tea & Seagreens) on cognitive function in older adults with subjective memory decline. Secondly, to investigate whether effects are underpinned by shifts in microbial composition and/or metabolism of the herbs. Methods: Male and female participants (N=128) aged between 55-75 years completed lab-based cognitive assessments, and provided stool and urine samples, at baseline and then following 90 days of multi-ingredient herb, or placebo, supplementation. Results: Deficits in memory were observed in response to 90 days of multi-ingredient herbal supplement supplementation but the positive effects were all focused on speed of cognitive task performance, with an additional improvement in the false alarm rate on the rapid visual information processing task. These improvements coincided with an increased presence of tyrosine in the urinary metabolome and this may implicate the role of dopamine in these processing and/or motor speed increases. Finally, multi-ingredient herbal supplementation significantly reduced levels of 3 bacterial species in the gut microbiome and one of these, Sutterella, coincides with lower levels of constipation reported in the multi-ingredient herbal supplement condition. Conclusions: A multi-ingredient herbal supplement increases speed of cognitive task performance and increased metabolism of tyrosine suggests that this is modulated by increased dopaminergic activity. Reduced levels of Sutterella in the gut is associated with improved bowel movements of participants. Interpretation of the negative effects on memory are, however, stymied by an unequal randomisation of participants into treatment groups pre- and post-Covid 19.